Effectiveness of health education interventions to improve malaria knowledge and insecticide-treated nets usage among populations of sub-Saharan Africa: systematic review and meta-analysis - Onyinyechi, Opara Monica; Mohd Nazan, Ahmad Iqmer Nashriq; Ismail, Suriani (Frontiers Media, 2023)
Introduction: Malaria health education intervention is a community-directed approach that has long been considered important in preventing malaria in sub-Saharan Africa. However, its effectiveness is being questioned due to a lack of strong evidence. We aim to synthesize the evidence of the impact of health education on malaria knowledge and insecticide-treated nets (ITN) usage. Specifically, we analyzed the odds of correctly answering malaria-related questions and the odds of using ITN between the intervention and control groups. Methods: Experimental and observational studies conducted in sub-Saharan Africa between 2000 and 2021 which had quantitatively evaluated the impact of health education interventions on malaria knowledge and ITN usage were included in the review. Results: A total of 11 studies (20,523 participants) were included. Four studies used educational interventions to teach appropriate ITN strategies and promote ITN usage. Two others focused on improving knowledge of malaria transmission, prevention, treatment, and its signs and symptoms. The remaining five studies assessed both ITN use and malaria knowledge. Of these, 10 were eligible for meta-analysis. On average, the odds of a person in the intervention group reporting better malaria knowledge (odds ratio 1.30, 95 CI: 1.00 to 1.70, P= 0.05) and higher ITN usage (odds ratio 1.53, 95 CI: 1.02 to 2.29, P= 0.004) increased significantly after receiving health education interventions compared to those in the control group. The odds of ITN usage also substantially increased when the interventions were based on a theory or model (odds ratio 5.27, 95 CI: 3.24 to 8.58, P= 0.05). Discussion: Our review highlights sub-Saharan Africa's various health education strategies to curb malaria over the past two decades. Meta-analysis findings show that health education interventions are moderately effective in improving malaria knowledge and ITN usage and have contributed to the effort of global malaria strategy.